Activity or connectivity? A randomized controlled feasibility study evaluating neurofeedback training in Huntington's disease. Issue 1 (23rd April 2020) - Papoutsi, Marina; Magerkurth, Joerg; Josephs, Oliver; Pépés, Sophia E; Ibitoye, Temi; Reilmann, Ralf; Hunt, Nigel; Payne, Edwin; Weiskopf, Nikolaus; Langbehn, Douglas; Rees, Geraint; Tabrizi, Sarah J
Abstract: Non-invasive methods, such as neurofeedback training, could support cognitive symptom management in Huntington's disease by targeting brain regions whose function is impaired. The aim of our single-blind, sham-controlled study was to collect rigorous evidence regarding the feasibility of neurofeedback training in Huntington's disease by examining two different methods, activity and connectivity real-time functional MRI neurofeedback training. Thirty-two Huntington's disease gene-carriers completed 16 runs of neurofeedback training, using an optimized real-time functional MRI protocol. Participants were randomized into four groups, two treatment groups, one receiving neurofeedback derived from the activity of the supplementary motor area, and another receiving neurofeedback based on the correlation of supplementary motor area and left striatum activity (connectivity neurofeedback training), and two sham control groups, matched to each of the treatment groups. We examined differences between the groups during neurofeedback training sessions and after training at follow-up sessions. Transfer of training was measured by measuring the participants' ability to upregulate neurofeedback training target levels without feedback (near transfer), as well as by examining change in objective, a priori defined, behavioural measures of cognitive and psychomotor function (far transfer) before and at 2 months after training. We found that the treatment group had significantly higher neurofeedback training target levels during the training sessions compared to the control group. However, we did not find robust evidence of better transfer in the treatment group compared to controls, or a difference between the two neurofeedback training methods. We also did not find evidence in support of a relationship between change in cognitive and psychomotor function and learning success. We conclude that although there is evidence that neurofeedback training can be used to guide participants to regulate the activity and connectivity of specific regions in the brain, evidence regarding transfer of learning and clinical benefit was not robust. Abstract : We evaluated feasibility of real-time functional magnetic resonance imaging neurofeedback training in Huntington's disease. The treatment group learned to regulate the neurofeedback target, activity or connectivity, compared to sham neurofeedback. However, evidence of transfer was weak. The treatment group did not self-regulate the target without neurofeedback better than controls; there was no improvement in behaviour. Graphical Abstract: